0121 Sounds Optimization To Maximize The Driving Of Slow Oscillations By Auditory Closed-loop Stimulations. (27th April 2018) - Debellemaniere, E; Pinaud, C; Schneider, J; Galtier, M N; Casson, A; Chennaoui, M; Arnal, P J; Lewis, P
Abstract: Introduction: Recent studies have shown that slow oscillations (SO) can be driven by auditory closed-loop stimulations to deepen slow wave sleep (SWS) and thereby improve memory and the immune-supportive hormonal milieu related to this sleep stage. While different attempts have been made to optimize the driving of the SO by changing the number of stimulation, no study has investigated the effects of the type of sounds on SO. Methods: Twenty healthy subjects (6M; aged 18–23 y.o) performed one night of closed-loop stimulation protocol in a sleep laboratory. Sequences of 10 pink noises, 10 pure sounds (B note of 247 Hz), 10 pronounced "A" vowels and 10 shams were targeted at the Up phase of the endogenous SO within a night. The effects of type of sound on SO and spindles were assessed by analysing the power, area under the curve, amplitude, slopes and event-related potentials. Results: We observed that all three tested sounds increased amplitude, area under the curve, power and slopes of SO and slow spindles compared to shams. However, pink noise elicited a significant much stronger effect compared to the other sounds, which was explained by a broader topographical recruitment of brain areas. Conclusion: The present study showed that rich sounds (i.e. pink noise) elicited a stronger SO driving than poor sounds. This type of sound may strongly trigger the simultaneous depolarization of neurons widely distributed over the cortex. Pattern of sequences using this rich sound, potentially in combination with other, have still to be optimized. Support (If Any): Ms ED is funded by a CIFRE-Defense PhD fellowship. ED, CP, MNG, PJA are employees of Rythm.